Pengaruh Likuiditas, Leverage, dan Profitabilitas terhadap Kualitas Laba dengan Ukuran Perusahaan sebagai variabel Moderasi pada Perusahaan Manufaktur - Aprilianti, Dhea; Kismayanti Respati, Dwi; Fauzi, Achmad (LPPM Universitas Negeri Jakarta, 2024)
This study aims to analyze the influence of liquidity, leverage, and profitability on the quality of earnings, taking into account company size as a moderating factor. The study examined publicly listed food and beverage companies on the Indonesia Stock Exchange. During that period, we utilized a purposive sampling strategy to identify 53 enterprises in the sector. The data was subjected to moderated regression analysis using IBM SPSS 26 software. The results suggest that liquidity and leverage have a negative and statistically significant effect on the quality of earnings, while profitability has a positive and substantial influence. Moreover, research has shown that the size of the organization influences the relationship between liquidity, leverage, profitability, and profit quality. The study aims to provide management and business owners with valuable insights into profit quality analysis and enhancement, thereby attracting investor attention. Furthermore, these outcomes could influence suppliers and creditors' decisions to extend credit to the company, while investors may take them into account when making investment decisions.